2022
DOI: 10.3389/fenvs.2022.848134
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Efficiency of Grass-Based Livestock Husbandry Under the Background of Rural Revitalization: An Empirical Study of Agro-Pastoral Ecotone

Abstract: As the starting point of addressing the issue of “agriculture, rural areas, and farmers” for a new era, a rural revitalization strategy is necessary and suits the realistic demand for high-quality development. At present, agro-pastoral ecotone in China is facing a series of ecological degradation and environmental pollution problems. The measurement and analysis of ecological efficiency play an important role in promoting the sustainable development of the agro-pastoral ecotone. Based on the theoretical discus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
0
4
0
1
Order By: Relevance
“…Different scholars have different approaches to the way heritage is monitored, and various monitoring efforts are basically carried out with individual indicators as monitoring factors [12,13]. Ecological environment quality measurement methods mainly include two types: one is single-factor change analysis, such as analysis of changes in factors closely related to ecological environment such as land use change [14,15], net primary production (NPP) [16] and ecoefficiency change [17]. The other type is multi-factor change integrated analysis, which is more comprehensive and accurate compared with single-factor analysis, and scholars have proposed various evaluation index systems for this purpose [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Different scholars have different approaches to the way heritage is monitored, and various monitoring efforts are basically carried out with individual indicators as monitoring factors [12,13]. Ecological environment quality measurement methods mainly include two types: one is single-factor change analysis, such as analysis of changes in factors closely related to ecological environment such as land use change [14,15], net primary production (NPP) [16] and ecoefficiency change [17]. The other type is multi-factor change integrated analysis, which is more comprehensive and accurate compared with single-factor analysis, and scholars have proposed various evaluation index systems for this purpose [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, farmland in APENC has been reduced by 9.05 × 10 3 km 2 from 2000 to 2018 in the context of ERPs, while the popularization of artificial forage grass increased the source of high‐quality feed, reducing the marginal cost for farmers to expand the amount of livestock, and thereby greatly increasing farmers' income and developing the economy of APENC (Gao et al, 2021; Meng et al, 2012; Yang, Dietz, et al, 2018). Therefore, grass‐based livestock husbandry combines both ecological and socioeconomic benefits, is an effective way to achieve sustainable development in APENC, and has become an important supporting industry in China's targeted poverty alleviation and rural revitalization strategies (Contributing Editor, 2021; Gao et al, 2019; Gao et al, 2021; He et al, 2022). Some localized studies have shown that ‘planting for husbandry support’ has become a common livelihood pattern for farm households in the APENC (Meng et al, 2012; Wang, Sun, & Ding, 2019; Zhu et al, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…Thus, it is an important way to increase the total output value of the livestock industry in China, develop the rural economy, and increase the income of farmers and herders (Gao et al, 2021; Meng et al, 2012; Xu et al, 2020). Therefore, grass‐based livestock husbandry is an effective way to achieve sustainable development in APENC, taking into account both ecological and socioeconomic benefits, and has become an important support industry in China's targeted poverty alleviation and rural revitalization strategy (Contributing Editor, 2021; Gao et al, 2019; Gao et al, 2021; He et al, 2022). In recent years, continuous in‐depth research by scholars (Fang et al, 2018b; Fang, Bai, et al, 2016) has driven the Government to promulgate a series of relevant policies, e.g., the slogan “Accelerate the development of grass‐based livestock husbandry” was formally proposed in China's Central Document in 2015 (Contributing Editor, 2021), and related pilot development trials were carried out nationwide (MARAC, 2016b).…”
Section: Methodsmentioning
confidence: 99%